2011
DOI: 10.1103/physreva.84.053607
|View full text |Cite
|
Sign up to set email alerts
|

Quantized vortices in a rotating Bose-Einstein condensate with spatiotemporally modulated interaction

Abstract: We present theoretical analysis and numerical studies of the quantized vortices in a rotating Bose-Einstein condensate with spatiotemporally modulated interaction in harmonic and anharmonic potentials, respectively. The exact quantized vortex and giant vortex solutions are constructed explicitly by similarity transformation. Their stability behavior has been examined by numerical simulation, which shows that a new series of stable vortex states (defined by radial and angular quantum numbers) can be supported b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 63 publications
0
36
0
Order By: Relevance
“…Such initial wave functions are widely used for the study of singly, doubly, or multiply quantized vortices [11,22,52]. As bases of the present work, the exact stationary solutions of ring vortex solitons with topological phases have been proposed in the nonrotating [28] and rotating BEC framework [29]. It is shown that when the initial state is the exact stationary solutions with topological charge, the stability and the number of vortices are almost the same for both rotating and nonrotating BECs.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Such initial wave functions are widely used for the study of singly, doubly, or multiply quantized vortices [11,22,52]. As bases of the present work, the exact stationary solutions of ring vortex solitons with topological phases have been proposed in the nonrotating [28] and rotating BEC framework [29]. It is shown that when the initial state is the exact stationary solutions with topological charge, the stability and the number of vortices are almost the same for both rotating and nonrotating BECs.…”
Section: Discussionmentioning
confidence: 86%
“…The radial excited state is of multiple concentric density-wave rings, i.e., n 2, and here we call it the multiple ring vortex soliton (MRVS). The one-dimensional (1D) and 2D solutions of the MRVS are also proposed for a specific, spatially modulated nonlinearity [27][28][29]. In experiments, the ringlike excitations have been observed in the hyperfine states |F = 1,m f = −1 and |F = 2,m f = +1 of 87 Rb under a rotating cylindrical magnetic trap [8].…”
Section: Introductionmentioning
confidence: 98%
“…For the case of = 2 we demonstrate some novel nonlinear structures by choosing the arbitrary function ( 1 + 2 + 0 + 3 ) specially. The separation transformation method may also be useful to solve other nonlinear wave models to explain the nonlinear excitations and localized nonlinear wave structures [19][20][21][22][23] in the physics of elementary particles and fields.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the system can be reduced to quasi-two-dimensional by considering a very strong confinement along z axis, i.e. ÿω z being much larger than any other energy scale [42][43][44][45][46], which is easily realized in the experiments, e.g. the experiments of Kwon et al [20][21][22][23].…”
Section: Formulation Of the Problemmentioning
confidence: 99%